Borders and economic growth : The case of Sabah and her neighbours - Muzafar, Shah Habibullah; Dayang Affizzah, Awang Marikan (Munich University Library, 2014)
Disparity in income across states and regions in Malaysia continues to be a matter of concern. The purpose of the present study is to investigate empirically the question of whether the economic development of the state of Sabah has an impact on her neighbouring countries or vice versa, the growth of her neighbouring countries have causal effect on the growth of the state of Sabah. Using annual data for the period 1983 to 2003, our results from employing the ARDL bounds testing approach indicate that the growth of the state of Sabah is affected by the growth of Brunei Darussalam, Sarawak, and Kalimantan Timur. Further, the growth of the state of Sabah has an impact on her neighbouring states, country and provinces during the period under study.